Ensaios sobre o efeito da interação de pesquisa e desenvolvimento e índice book-to-market no desempenho do mercado de ações: evidências para empresas brasileiras - Rezende, Cláudio Francisco (2021)
This analysis of the impact of innovation and company value on the performance of Brazilian companies in the stock market. Specifically, the objective of this analysis was analyzed, in an unprecedented way, the contribution of spending on research and development together with the market value, having as a proxy the book-to-market (BM) index, on the return and on the abnormal return of the shares of publicly traded Brazilian companies listed on the Brasil Bolsa Balcão (B3) stock exchange. The main theoretical bases used were extracted from the literature of the themes, through a theoretical review of the main authors and existing portfolio theories in the economic-financial literature on the construction of portfolios to price assets through econometric tests of risk-premium factors of investing in stocks. The theoretical review will clarify the main fundamentals about the influence of research and development (R&D) on market performance and certify R&D expenditure as a substitute variable for innovative effort. The econometric method used by fixed effects regression of panel data investigated two effects in the second trial: i) the relationship between research and development and stock returns and ii) the relationship between the variation of the variation in research and development spending and value on stock returns. The results found were: i) the sample of R&D and stock returns of Brazilian companies have a negative and statistically significant relationship at a 5% confidence level in current periods and ii) there is no statistically significant relationship between the variation in R&D combined with the market value in shareholder returns. No third essay uses the double portfolio classification method and cross-section regression of the constructed portfolios to test, empirically, the joint relationship of R&D expenditure and value in the generation of abnormal returns in the stock market. The asset pricing models for the formation of efficient portfolios, used to capture abnormal returns in the stock market were: i) 3-factor and 5-factor models by Fama and French (1993; 2015) and ii) 4-factor model by Carhart ( 1997). The main results found were: i) for stock market investment analysis, it is important for investors to monitor the performance of portfolios consisting of high R&D intensity and high degree of BM, which generate greater future cash flows and enable more expected returns high; ii) in the 3, 4, and 5 factor models, statistically relevant relationships were identified in the portfolios built by market, size, value, momentum, profitability, and investment factors and iii) the existence of abnormally high returns in the market was detected. shares of Brazilian companies listed on B3, but only in companies that are intense in R&D and with a medium or high degree of BM, and that in companies that are intensive in R&D, there is a reinforcement in relation to the average value by BM over the excess return of shareholders.